2000
DOI: 10.1039/b006285p
|View full text |Cite
|
Sign up to set email alerts
|

Determination of titanium dioxide in foods using inductively coupled plasma optical emission spectrometry

Abstract: Titanium dioxide is a common food additive of increasing interest in dietary intake studies and dietary exclusion studies. Food labelling for titanium dioxide is imprecise so a method was developed for its rapid determination in foods using acid digestion and inductively coupled plasma optical emission spectrometry (ICPOES). Twenty-five foods thought to contain titanium dioxide were obtained. Based on preliminary digestion studies, samples (500 mg) were digested in 18 mol l-1 H2SO4 at 250 degrees C for 1 h and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(120 citation statements)
references
References 10 publications
3
113
0
4
Order By: Relevance
“…For example, labelling is not required when additives perform no additive function in the final product and are used in compound ingredients that make up less than 25 % of the finished product (Lomer et al 2000). In addition, of course, many foods purchased as ready-to-eat do not carry food labels.…”
Section: Sources Of Exogenous Dietary Microparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, labelling is not required when additives perform no additive function in the final product and are used in compound ingredients that make up less than 25 % of the finished product (Lomer et al 2000). In addition, of course, many foods purchased as ready-to-eat do not carry food labels.…”
Section: Sources Of Exogenous Dietary Microparticlesmentioning
confidence: 99%
“…Indeed, an individual's dietary choices or preferences will dictate their intestinal exposure to TiO 2 . In extreme cases just one portion of a salad dressing (225 mg TiO 2 ; Lomer et al 2000) could exceed the average daily intake of 5·4 mg (Ministry of Agriculture, Fisheries and Food, 1993) by > 40-fold.…”
Section: Sources Of Exogenous Dietary Microparticlesmentioning
confidence: 99%
“…It is the brightest known white pigment and, in foods, it provides a basic white background colour that acts as an opacifier, and reflects light across most of the visible spectrum. It may also act as a barrier by physically separating other colours (Lomer et al, 2000). TiO 2 is authorised as a food colour in the European Union (EU) as E 171 (EU, 2011a) and is commonly used as a food additive (Peters et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the International Agency for Research on Cancer has concluded that while there is inadequate evidence of the carcinogenicity of TiO 2 in humans, there is sufficient evidence from studies in experimental animals, and has thus classified titanium dioxide as a Group 2B compound (possibly carcinogenic to humans) 1) . In general, however, TiO 2 has been regarded as inert and is added to cosmetics, toothpaste, drugs and foods 8) . It has often been used as a negative control in experiments on the effects of particles or fibers in cells and animals 9,10) .…”
mentioning
confidence: 99%